(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A study was conducted to investigate the effects of bamboo vinegar liquid with beneficial microbes (probiotics), BVLP on growth performance, meat composition, and thiobarbituric acid (TBA) value. A total of 175 one day old Ross broiler chicks were distributed to 5 treatments having 5 replications with 7 chicks in each, following a completely randomized design. The treatments were: control (basal), antibiotic (basal+30 ppm Oxytetracycline), bamboo vinegar liquid probiotics (basal+0.2%, basal+0.4% and basal+0.8%). Significantly lowest feed intake was recorded in 0.4% BVLP compared to 0.8% BVLP group although highest weight gain was observed in 0.2% BVLP among the BVLP groups(P<0.05). Significantly highest protein percentage in broiler meat fed BVLP (0.2 and 0.4%) were recorded compared to 0.8% and antibiotic fed diet (P<0.05). Crude fat significantly reduced in 0.2% BVLP group than control and antibiotic group. Statistically similar values in fresh meat TBA were observed in 0.2 to 0.4% BVLP fed broilers with antibiotic group except 0.8% BVLP diet (P<0.05). After 3 weeks preservation no statistical differences were observed among the treatments, that indicates no detrimental effects observed after addition of BVLP. Significantly lowest abdominal fat was found in 0.2% BVLP compared to antibiotic group (P<0.05). Significantly highest length of large intestine was recorded in 0.8% BVLP compared to control and 0.4% BVLP groups (P<0.05). Considering the findings, bamboo vinegar liquid probiotics can be replaced instead of antibiotic and BVLP 0.2 to 0.4% may be the suitable level for broiler production. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 483-491